Implementation of Chopper Fed Speed Control of Separately Excited DC Motor Using PI Controller (International Journal of Engineering and Computer Science, 2017)
This paper presents a speed control of a separately excited DC motor by using PI (Proportional Integral). The speed of the separately excited DC motor can be varied below and above the rated speed by various speed control techniques. It can be varied above the rated speed by field flux control and below the rated speed by armature terminal voltage control. The conventional controllers are commonly being used to control the speed of the DC motors in various industrial applications. It’s found to be simple, robust and highly effective, when the load disturbance is small. Here, we using chopper as a converter the speed of DC motor is controllable. The chopper firing circuit gets signal from controller and then by supplying variable voltage to the armature of the motor then to obtain the desired speed of the motor. There are two different types of control loops, current controller and speed controller. The controller used is ProportionalIntegral type. The current and speed controller loop is designed and in order to get stable and high speed control of DC motor. The simulation of the above model is done in MATLAB/SIMULING under varying speed and torque condition.